Metal-phthalocyanine ordered layers on Au(110): Metal-dependent adsorption energy - Massimi, Lorenzo (2014)
Iron-phthalocyanine and cobalt-phthalocyanine chains, assembled along the Au(110)-(1×2) reconstructed channels, present a strong interaction with the Au metallic states, via the central metal ion. X-ray photoemission spectroscopy from the metal-2p core-levels and valence band high-resolution ultraviolet photoelectron spectroscopy bring to light signatures of the interaction of the metalphthalocyanine single-layer with gold. The charge transfer from Au to the molecule causes the emerging of a metal-2p core level component at lower binding energy with respect to that measured in the molecular thin films, while the core-levels associated to the organic macrocycle (C and N 1s) are less influenced by the adsorption, and the macrocycles stabilize the interaction, inducing a strong interface dipole. Temperature Programmed Desorption experiments and photoemission as a function of temperature allow to estimate the adsorption energy for the thin-films, mainly due to the moleculemolecule van der Waals interaction, while the FePc and CoPc single-layers remain adsorbed on the Au surface up to at least 820 K. © 2014 AIP Publishing LLC.